2011
DOI: 10.1007/s12088-011-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Production, Purification of Exo-Polygalacturonase from Soil Isolate Paecilomyces variotii NFCCI 1769 and Its Application

Abstract: The aim of the present study was to produce exo-polygalacturonase from potent soil isolate by submerged fermentation and its application for fruit juice treatment. Pectinase producing strains were selectively isolated from pectin industry waste. A selected isolate C2 was found to produce significant amount of exo-polygalacturonase. The isolate was identified as Paecilomyces variotii on the basis of morphological characteristics and 18S rRNA gene sequence analysis. The exo-polygalacturonase produced by the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
(17 reference statements)
2
21
3
Order By: Relevance
“…The specific activities of NfPG4 and NfPG5 on polygalacturonic acid were 700.9 and 3630.4 U/mg, respectively ( Table 2). The specific activity of NfPG4 is much higher than most exo-polygalacturonases such as that from P. variotii NFCCI 1769 (98.49 U/mg) [29], from A. niger (31.4 U/mg) [30], or from Butyrivibrio fibrisolvens (1.7 U/mg) [31]. The endopolygalacturonase NfPG5 is also a robust enzyme, with a specific activity of 3630.4 U/mg comparable to most characterized pectinases with high activities.…”
Section: Substrates and Chemicals Affecting The Pectinase Activitiesmentioning
confidence: 87%
“…The specific activities of NfPG4 and NfPG5 on polygalacturonic acid were 700.9 and 3630.4 U/mg, respectively ( Table 2). The specific activity of NfPG4 is much higher than most exo-polygalacturonases such as that from P. variotii NFCCI 1769 (98.49 U/mg) [29], from A. niger (31.4 U/mg) [30], or from Butyrivibrio fibrisolvens (1.7 U/mg) [31]. The endopolygalacturonase NfPG5 is also a robust enzyme, with a specific activity of 3630.4 U/mg comparable to most characterized pectinases with high activities.…”
Section: Substrates and Chemicals Affecting The Pectinase Activitiesmentioning
confidence: 87%
“…The enzyme delivered a considerable reduction in the viscosity of fruit juice samples (Patil et al . ).…”
Section: Pectinasesmentioning
confidence: 97%
“…), chitinases (Saad and Hamdy ), pectinases (Patil et al . ), phytases (Schons et al . ), tannases (Macedo et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cultures incubated for long periods may lead to depletion of nutrients, cell death of the fungus and degradation of the enzymes (PELCZAR et al, 1996). Maciel et al (2013) observed that the highest PG production by A. nigri occurred between 48 and 96 h and Patil et al (2012) observed that 72 h was the optimal cultivation time for exo-PG production by Paecilomyces variotii.…”
Section: Effect Of Cultivation Temperature and Time-coursementioning
confidence: 99%
“…Laorko et al (2010) also used the enzymatic treatment of apple juices before micro-and ultrafiltration tests. Patil et al (2012) tested an exo-PG produced by Paecilomyces variotii in the treatment of fruit juices, and observed viscosity decreases in orange, apple, grape, banana and guava juices. Tu et al (2013) reported a 17.6% viscosity reduction in papaya juice with the application of an endo-PG.…”
Section: The Application Of the Enzymatic Extract In Fruit Juice Procmentioning
confidence: 99%